Neovascularization After Irradiation: What is the Source of Newly Formed Vessels in Recurring Tumors? - Kozin, Sergey V. (Oxford University Press, 2012)
Local relapse of tumors after radiation therapy remains a challenge in oncology. To devise rational approaches for preventing this relapse, we have to improve our understanding of how new vessels form in previously irradiated tumors. We propose that tumor regrowth after local irradiation is dependent on blood vessel formation by local endothelial cells without the need for recruitment of endothelial precursor cells from distant nonirradiated tissues or bone marrow. We also suggest that infiltrating myeloid bone marrow–derived cells promote survival of local endothelial cells during the early period after irradiation and angiogenesis during the later stage of tumor regrowth, both via paracrine mechanisms.